Building Research Data Management Infrastructure using Open Source Software. Issue 4 (23rd September 2013) - Willmes, Christian; Kürner, Daniel; Bareth, Georg
Abstract The implementation of a research data management infrastructure for a large interdisciplinary research project is presented here, based on well‐established Free and Open Source Software for Geospatial (FOSS4G) products such as MapServer, MapProxy, GeoExt and pyCSW, as well as the (not primarily geospatial) open source technologies Typo3 and CKAN. The presented implementation depends primarily on the demands for research data management infrastructure by the funding research agency. It also aligns to theory and practice in Research Data Management (RDM) and e‐Science. After the research project and related work in the field of RDM are introduced, a detailed description of the architecture and its implementation is given. The article discusses why Open Source and open standards are chosen to implement the infrastructure and provides some suggestions and examples on how to make it easier and more attractive for researchers to upload and publish their primary research data.